Ultra-broadband and wide-angle plasmonic light absorber based on all-dielectric gallium arsenide (GaAs) metasurface in visible and near-infrared region - Cai, Bin; Wu, Ling; Zhu, Xinwang; Cheng, Zhengze; Cheng, Yongzhi (Results in physics, 2024)
•An ultra-broadband and wide-angle plasmonic light absorber (PLA) based on GaAs metasurface at optical frequency is proposed.•The proposed PLA achieves absorbance over 90 % from 0.39 μm to 2.09 μm with a relative bandwidth of 137.1 %, the absorption peak over 99 %, and also a remarkable short-circuit current density of over 64.75569 mA/cm2.•The ultrabroadband strong absorption of the proposed PLA can be illustrated by the equivalent circuit model (ECM), which agrees well with the numerical simulation using the FEM.•The ultra-broadband strong absorption of the designed PLA is mainly from the propagating surface plasmon (PSP), located surface plasmon (LSP), cavity resonance modes combined with coupling effect. High-performance and cost-effective broadband light absorbers are crucial for various optical applications, including solar energy harvesting, thermophotovoltaic systems, and integrated photoelectric devices. In this study, an ultra-broadband and wide-angle plasmonic light absorber (PLA) based on an all-dielectric gallium arsenide (GaAs) metasurface in the visible and near-infrared regions is proposed and numerically investigated. The unit-cell of the proposed PLA is consisted of all-dielectric GaAs cylinder resonator (CR) adhered on an ultra-thin GaAs spacer layer backed with a tungsten (W) substrate. Numerical simulation results show that the absorption peak of the proposed PLA is up to 99.85 %, 99.9 % and 99.98 % at 0.452 μm, 0.712 μm and 1.596 μm, respectively. In addition, the ultra-broadband strong absorption of over 90 % also can be achieved from 0.39 μm to 2.09 μm with a relative bandwidth of 137.1 %. The ultrabroadband strong absorption of the proposed PLA is further demonstrated by the equivalent circuit model (ECM), which displays excellent agreement with the results of the full-wave numerical simulation performed using the finite element method (FEM). The simulated electromagnetic (EM) field distributions reveal that the ultra-broadband strong absorption of the designed PLA is mainly from the excited propagating surface plasmon (PSP), located surface plasmon (LSP), cavity resonance modes combined with coupling effect between adjacent CRs. The proposed PLA is also polarization-insensitive and wide incident angles for both transverse electric (TE) and transverse magnetic (TM) modes. The absorption properties of the designed PLA can be adjusted by varying geometric parameters of the unit-cell. The PLA achieves a remarkable short-circuit current density of over 64.75569 mA/cm2 and exhibits nearly perfect solar energy trapping due to the effective coupling of multiple resonances, resulting in enhanced photovoltaic performance. Thus, the proposed PLA can be potential application in the photodetectors, thermal imaging, and solar energy harvesting devices.